Increased Serum Levels of Proinflammatory Cytokines Are Accompanied by Fatigue in Military T-6A Texan II Instructor Pilots - Damato, Elizabeth G.; Fillioe, Seth J.; Margevicius, Seunghee P.; Mayes, Ryan S.; Somogyi, Jonathan E.; Vannix, Ian S.; Abdollahifar, Alireza; Turner, Anthony M.; Ilcus, Lidia S.; Decker, Michael J. (Frontiers in Physiology, 2022)
Tactical aviation imposes unprecedented physical challenges including repetitive exposure to hypergravity, hyperoxia, increased work of breathing, and profound cognitive workloads. Each stressor evokes outcomes ranging from musculoskeletal duress and atelectasis to physical and cognitive fatigue, the latter among the foremost threats to aviators. Whereas sleep loss is traditionally considered the primary cause of fatigue in aviators, converging experimental, observational, and medical studies have identified biochemical mechanisms promoting onset of fatigue. Those mechanisms, which fundamentally differ from sleep loss, revolve around increased proinflammatory cytokines, produced and released in response to tissue injury, chronic inflammatory disorders, allergens, or physical duress. This study’s objective was to inform our understanding of potential relationships between serum levels of proinflammatory cytokines and onset of fatigue within a cohort of aviators who experience multiple high-performance sorties on a daily basis. Methods: Active duty and reservist T-6A Texan II instructor pilots were studied on three separate days across their week-long flying schedule. Data collected included a physical assessment, subjective fatigue levels, venous blood samples for measures of chemistry and serum analytes, and urine samples for specific gravity. Results: Twenty-three persons were studied, of which 22 fulfilled minimum study requirements of completing two sorties. The study cohort was comprised of primarily males, age 37.95 ± 4.73 years with a BMI of 26.63 ± 3.15 kg/m2. Of 37 measurable serum analytes, 20 differed significantly (p < 0.05) between baseline values with those measured at the study endpoint. Thirteen of the aviators reported increased fatigue scores across their flying schedule whereas nine did not. Eleven blood serum analytes were associated with increasing levels of fatigue. Discussion: Fatigue in aviators has been attributed almost solely to sleep loss, nocturnal sorties, or disrupted circadian rhythmicity. In contrast, our study findings suggest an alternative mechanism that can promote onset of fatigue: increased blood levels of proinflammatory cytokines. Specific mechanisms triggering synthesis and release of those cytokines and other analytes are yet to be determined. However, their expression patterns suggest responses to both chronic and acute inflammation, hyperoxia, or bronchopulmonary responses to inspiration of dry gas, positive airway pressure, or perhaps atelectasis.